2011
DOI: 10.1007/s00066-011-2283-x
|View full text |Cite
|
Sign up to set email alerts
|

Radiotherapy for Prevention and Therapy of Gynecomastia Due to Antiandrogen Treatment in Prostate Cancer Patients

Abstract: Prophylactic and symptomatic RT is widely used in the German-speaking countries, but patient numbers are small. The clinical results indicate that RT is a highly effective and well-tolerated treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 30 publications
(34 reference statements)
0
4
0
2
Order By: Relevance
“…Unfortunately, there is no evidence from randomized trials available regarding different fractionation schedules of RT neither as a prophylactic or therapeutic treatment. Today, besides the established 1 × 10-12 Gy single shot treatment, or the 2 × 6 Gy schedule, commonly hypofractionated schedules with 3-5 fractions of 3 Gy are applied, as recently reviewed by the guideline for radiotherapy of benign diseases published by the German Society for Radiation Oncology (DEGRO) and others [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, there is no evidence from randomized trials available regarding different fractionation schedules of RT neither as a prophylactic or therapeutic treatment. Today, besides the established 1 × 10-12 Gy single shot treatment, or the 2 × 6 Gy schedule, commonly hypofractionated schedules with 3-5 fractions of 3 Gy are applied, as recently reviewed by the guideline for radiotherapy of benign diseases published by the German Society for Radiation Oncology (DEGRO) and others [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…First, Germany now has 340 active centers, compared with 152 in 1996. Because several studies have demonstrated the effectiveness of RT for benign diseases, 3 , 4 , 5 , 6 , 7 , 8 , 9 , 14 , 15 , 16 , 17 , 18 , 19 RT is commonly used for several benign indications. In comparison with the first PCS, there is no change within the treatment concepts but rather a change in indications.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, many German publications reflect the significance of RT across the country, 3 , 4 , 5 which is due primarily to the foundation of the German Cooperative Group on Benign Diseases (GCG-BD) in 1996 by the German Society for Radiation Oncology (DEGRO). This group was founded to train physicians in the treatment of benign diseases, coordinate scientific work and clinical trials, and improve experience within this entity.…”
Section: Introductionmentioning
confidence: 99%
“…Die in der Literatur beschriebenen Dosiskonzepte zeigen eine große Spannbreite, Daten von dosisvergleichenden Untersuchungen sind für die Strahlentherapie nicht verfügbar. Eine Patterns-ofcare-Studie der DEGRO-AG für die Strahlentherapie gutartiger Erkrankungen (GCG-BD) zeigte, dass die in Deutschland eingesetzten Dosen für die prophylaktische Bestrahlung zwischen 9-24 Gy variierten, zumeist jedoch hypofraktionierte Bestrahlungsserien mit 12-15 Gy in 3-5 Fraktionen zur Anwendung kommen [554]. Literaturdaten belegen, dass geringere Dosen, wie zum Beispiel 4 x 1,5 Gy mit deutlich schlechteren Ansprechraten (18,4 %) einhergehen [664].…”
Section: Dosiskonzept/rt-technikunclassified